Potret Ekstrakurikuler Forum Annisa Dalam Memperbaiki Karakter Siswa Perempuan - Aisyah Cantika; Nurjanah Nurjanah; Hifdhotul Munawwaroh (An-Nuha, 2025)
The formation of female students' character is very important in facing social, cultural, and social challenges in the modern era. The Annisa Forum at SMA Negeri 12 Padang plays a role in forming students' character through strengthening Islamic values, discipline, leadership, and social awareness. This study aims to understand the school's efforts in forming the character of female students through the Annisa Forum, identify the forms of activities carried out, and analyze the obstacles in its implementation. This study uses a qualitative method with a case study approach. Data were collected through observation, interviews with the school and students, and documentation analysis. The results of the study indicate that character formation is carried out through motivation and habituation. Annisa Forum activities include opening, delivering materials, question and answer sessions, and closing. The obstacles faced include limited space, lack of mentors, low student awareness, lack of methods and media, minimal teacher supervision, and lack of firmness in implementing attendance rules. In conclusion, the Annisa Forum has an important role in forming the character of female students, but still requires improvements in facilities, methods, and supervision to be more effective.